The Influence of Work Motivation, Work Environment, and Work Culture on Employee Performance at Rensa Sofyan Hotel - Darda, Ahmad; Rojikun, Ahmad (Manunggal Halim Jaya, 2025)
This study investigates the influence of Work Motivation, Work Environment, and Work Culture on Employee Performance at Rensa Sofyan Hotel, a three-star hotel located in East Jakarta. The research was conducted in response to a noticeable decline in employee performance over the years 2020 to 2022. Using a quantitative research approach, data were collected through the distribution of structured questionnaires to employees. The population in this study consisted of all employees at Rensa Sofyan Hotel, and a sample of 40 respondents was selected for analysis. The variables measured include work motivation (X1), work environment (X2), work culture (X3), and employee performance (Y), with each measured using a five-point Likert scale. Data analysis techniques included validity and reliability tests, normality test, F-test, t-test, and coefficient of determination (R²). The results revealed that work motivation had a positive and significant effect on employee performance, while work environment and work culture showed no significant effect when tested individually. However, when analyzed simultaneously, all three independent variables had a significant joint influence on performance. The study concludes that employee motivation plays a dominant role in shaping performance outcomes, offering useful implications for human resource management strategies in the hospitality sector.